Tanggung Jawab Hukum Perusahaan Asuransi dan Perlindungan Konsumen Pasca Pencabutan Izin Usaha - Mayang Asmara Megaputri, Vincencia; Hariyani, Iswi; Prakoso, Bhim (Magister Kenotariatan, Universitas Jambi, 2025)
The revocation of PT Asuransi Jiwa Adisarana Wanaartha's business licence by OJK on 5 December 2022 was due to violations of solvency, investment adequacy ratio, and minimum equity requirements. The revocation of this business licence requires the company to undergo liquidation and has an impact on policyholders who face the risk of defaulting on claims. This research uses normative juridical method with statutory and conceptual approaches. The result of the discussion of the issues examined by the author is that the revocation of PT Asuransi Jiwa Adisarana Wanaartha's business licence by the OJK meant that the company lost its legal status to operate, resulting in a liquidation process aimed at settling the company's obligations and protecting the interests of policyholders. The consequences of the revocation of the business licence for policyholders include changes in the claims mechanism, which now proceeds through an administrative and uncertain liquidation process, as well as facing the risk of losses due to the company's limited assets. After its business licence was revoked, PT Asuransi Jiwa Adisarana Wanaartha is obligated to prioritise policyholders in settling its obligations, meaning the company must refund all premiums to policyholders due to the cancellation of the insurance agreement. Legal protection for policyholders is provided through the insurance policy as internal legal protection and external legal protection from the OJK and the Deposit Insurance Agency under the P2SK Law. In the event of a dispute, policyholders may resolve it through litigation by filing a breach of contract lawsuit if the company fails to fulfil the insurance agreement.